Features of EEG & HRV in 1997 in humans exposed to the factors of the accident at the Chornobylian nuclear power plant in 1986 - Ruzhylo, Sofiya; Zakalyak, Nataliya; Ivanikiv, Nataliya; Popovych, Dariya; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2022)
Background. The dramatic events of the Russian-Ukrainian war around the Chornobyl’ nuclear power plant (NPP) once again opened up the healed wound inflicted by radionuclides on the human body not only in Ukraine, but also in Belarus and the border regions of Russia. The drama of the situation was further intensified by the events surrounding the Zaporizhzhia NPP. This prompted us to turn to the archive of the Truskavetsian Scientific School of Balneology and process the results of research that, due to certain technical and ethical circumstances, remained unanalyzed. Material and methods. The cohort of observation in 1997 were 19 men and 3 women who were exposed to pathogenic factors of the accident at the Chоrnobylian nuclear power plant during the liquidation of its consequences in 1986. The subject of the study was EEG and HRV parameters. The survey was conducted twice - on admission and after two weeks of rehabilitation at the Truskavets’ Spa. Results. Screening of the registered parameters revealed a pronounced sympathotonic shift of the autonomic balance, as well as a statistically significant deviation from the norm of 18 EEG parameters (increase in 8 and decrease in 10). Under the influence of two-week balneotherapy, 5 increased and 5 decreased EEG parameters normalized, but the remaining abnormal EEG and HRV parameters were resistant to the influence of balneofactors. Conclusion. Neurophysiological disorders, detected even 11 years after the effects of the factors of the Chornobyl’ disaster, differ both in severity and sensitivity to the sanogenic effect of the adaptogenic factors of the Truskavets’ Spa.